Desain dan Realisasi Alat Ukur Kadar CO2 Portabel dengan Notifikasi Suara Berbasis Mikrokontroler Arduino - Nuryanto, M; Babys, Rosalia Maria; Marlin, Syamsu (Sistem Komputer dan Teknologi Intelegensi Artifisial (SIKOMTIA), 2023)
Increasing levels of carbon dioxide (CO2) in the environment is a global issue that has an impact on climate change and air quality. Easily accessible CO2 measurement is important for monitoring and mitigating these impacts. This research aims to design and realize a portable CO2 level measuring instrument with sound notifications, using an Arduino microcontroller. The method used in this study is the development of microcontrollers. CO2 analyzers are designed using CO2 sensors, microcontrollers and sound output modules. Data processing and calibration are performed to ensure measurement accuracy. Tests are conducted at various locations to assess the performance of the tool in real conditions. This portable device is integrated with an audible notification system that provides immediate alerts to users when CO2 levels exceed unnatural limits. Concern for urban communities efforts to increase awareness and response to adverse air conditions, especially in open spaces and urban environments. The results showed that portable CO2 analyzers were able to measure CO2 levels with good accuracy according to the specifications of the components used. The sound notification system works to provide alerts in various conditions. Portability, ease of use make this tool useful for individuals and simple to carry to monitor and respond to changes in air quality.